Usability Testing in Virtual Reality Based Interactive Film â€œCahaya Cinta Perlahan Menyilaukanâ€: English - Tinarbuko, Zul; Rahmiaty, Siti Adlina (Universitas Jember, 2024)
â€œCahaya Cinta Perlahan Menyilaukanâ€ is a virtual reality based interactive film produced by the Film and Animation department at Multimeda Nusantara University. This film was developed as an alternative way of learning vocational skills, especially in a film production environment. This film has two episodes and three difereent interactive levels to learn basic film lighthing. This study was conducted during the interal film premiere using a post survey questionnaire. The questionnaire contains a usability measure to determine how easy it is to experience the interactive film. Using two categories by Nielsen (1996) such as memorability and learnablity to measure usability, 44 attendees filled the survey. The overall result from the survey is beneficial to improve the succeeding version of the film.